Legionella-induced suppurative cervical lymphadenitis in a child diagnosed by metagenomic next-generation sequencing: a case report - Li, Bowen; Liao, Yaru; Li, Jian (Frontiers in Pediatrics, 2025)
Legionella pneumophila, primarily associated with respiratory infections, rarely causes extrapulmonary disease. Conventional diagnostic methods for Legionella are often limited. Here we report a case of suppurative cervical lymphadenitis caused by L. pneumophila. And we highlight the critical role of mNGS in enabling rapid and accurate pathogen identification, guiding effective targeted therapy for rare and challenging infections.